Organizational and functional lending model of sugar beet production in small farms - Shaporova, Yu G (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii︠a︡ agronomii︠a︡ i zhivotnovodstvo, 2015)
According to studies the main recipients of funds from the consolidated budget for the sugar industry are medium and large agricultural organizations and processing enterprises. Small forms of agricultural organizations, peasant (farmer) farms, private farms remain outside the scope of attention from the federal and regional authorities. This article discusses the direction to stimulate domestic producers of sugar beet production by creating cooperative associations, as well as proposed and substantiated organizational and functional model of lending to small farms.